Implementation of an OWC channel emulator in FPGA - Rodrigues, Luís (2021)
This paper discusses the feasibility and implementation of a complete Optical Wireless Communications (OWC) system emulator. The emulating platform comprises the ability to model all the key aspects of an OWC system, such as the emitter, the channel and the receiver. In order to implement the proposed architecture, Field-Programmable Gate Arrays (FPGAs) were chosen due to their flexibility and processing power. The proposed architecture operates in real time with a sampling frequency of 250MHz. The achieved results demonstrate the channel effects on signal transmission, allowing designers to improve system design from the early stages of the project. For illustration purposes, the results demonstrate the transmission of a 4-Quadrature Amplitude Modulation (QAM) Orthogonal Frequency Division Multiplexing (OFDM) modulated signal through the channel. As it is demonstrated, several important metrics, such as channel frequency response, bit error rates or signal constellations, are readily available, through a dedicated interface with Matlab.